Korelasi Antara Kecepatan dan Kelincahan Terhadap Keterampilan Dribbling Dalam Permainan Futsal - Deni Mudian; Arif Fajar Prasetiyo (Lembaga Pengembangan Kinerja Dosen, 2024)
. This study aims to determine the correlation between speed and dribbling skills in futsal games, this study uses a descriptive method with a correlational study. The population used is a futsal extracurricular club and a sample of 30 athletes. The instruments used in this research are speed measurement using a 40 meter run test), agility measurement using the Illinois agility run, and dribbling test. Based on the results of data processing carried out manually and with the help of SPSS 20 software, it can be concluded that there is a significant relationship of 0.858 and has an interpretation of the correlation coefficient value that speed has a very strong positive relationship to futsal dribbling skills and has a contribution of 70%. There is a significant relationship of 0.953 and has an interpretation of the correlation coefficient value that agility has a very strong positive relationship to futsal dribbling skills and has a contribution of 85.4%. There is a significant relationship of 0.965 and has an interpretation of the correlation coefficient value that speed and agility have a positive correlation to futsal dribbling skills and have a contribution of 88.5%. The conclusion is that there is a significant correlation between speed, agility and dribbling skills in futsal games.